1972
DOI: 10.1111/j.1365-246x.1972.tb06107.x
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Secular Variation During the Brunhes Epoch in the Indian and Atlantic Ocean Regions

Abstract: Brunhes epoch secular variation in the Indian and Atlantic Ocean regions has been examined using available and unpublished palaeomagnetic results from igneous rocks. Specimens from 401 separate units, all of which have unstable components minimized, are involved. More than half of these data are previously unpublished. The data are classified as fist order when the mean direction for each body is derived from at least four separate specimens, and second order when the number of specimens per body is not consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…All specimens were demagnetized in alternating magnetic fields of 100, 200, and 300Oe, and mean directions of stable remanent magnetism were computed using minimum dispersion computation methods (see Watkins, Hajash & Abranson 1972 for discussion). 2 3 3 3 3 3 3 2 2 3 2 3 3 3 3 3 3 3 3 2 4 4 4 Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…All specimens were demagnetized in alternating magnetic fields of 100, 200, and 300Oe, and mean directions of stable remanent magnetism were computed using minimum dispersion computation methods (see Watkins, Hajash & Abranson 1972 for discussion). 2 3 3 3 3 3 3 2 2 3 2 3 3 3 3 3 3 3 3 2 4 4 4 Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…This result is not surprising in so far as the remanence of the lava from Amsterdam is not contaminated by significant spurious components. This was not the case, for example, in a recent study on the volcanic sequence from Possession Island (Camps et al 2001), where the authors concluded that the intermediate directions initially described by Watkins et al (1972) correspond to reversed directions, which had been incompletely cleaned of their present‐day field viscous overprint. Here, we believe that the previously published data for Amsterdam Island (Watkins & Nougier 1973), which were not resampled in the present study are, equally reliable.…”
Section: Palaeodirection Determinationsmentioning
confidence: 99%
“…(Watkins et al, 1972), Crozet Is. (Watkins et al, 1972), Easter Is. (Isaacson and Heinrichs, 1976), France (Doell, 1970), Gulf of Guinea, (Piper and Richardson, 1972) Hawaii Is.…”
Section: Distribution Of Asdmentioning
confidence: 99%
“…(Watkins et al, 1972), Comores Is. (Watkins et al, 1972), Crozet Is. (Watkins et al, 1972), Easter Is.…”
Section: Distribution Of Asdmentioning
confidence: 99%